Analysis of Longevity Traits in Holstein Cattle: A Review - Hu, Honghong; Mu, Tong; Ma, Yanfen; Wang, XingPing; Ma, Yun (Frontiers in Genetics, 2021)
Dairy cow longevity is an essential economic trait that can supplement the breeding value of production traits and is related to the herd time and lifetime milk yield of dairy cows. It is more difficult to breed due to the low heritability and numerous influencing factors of the longevity in dairy cows. Longevity trait has been used as an important breeding target of comprehensive selection index in many dairy developed countries, but it has not been included in production performance index in China. At present, dairy cows in China are still in the primary stage of "large quantity, low quality, high cost and low output." The average parity of dairy cows is less than 2.7, the production life is short, culling is frequent, and it is difficult to maintain the production efficiency of dairy industry. Therefore, there is an urgency to select and breed the longevity of dairy cows. After analyzing the definition of longevity in different countries, there are many different models according to different definitions, such as linear, threshold, random regression, sire, survival analysis model. survival analysis is the optimal model to evaluate longevity, and longevity heritability is between 0.01 to 0.30. By summarizing the relationship between longevity and other traits, we found that longevity regulated by multiple factors, and there is a low to medium genetic correlation between each trait and longevity. It is suggested that the body type traits, milk production traits, reproductive traits and health traits should be used as indicators to measure the longevity of dairy cows and assist the selection and breeding of longevity. The genetic assessment methods, heritability, influencing factors, importance, breeding, related genes, and molecular markers of longevity were reviewed in this paper, with the aim of providing references for the selective breeding to extend the productive life of Holstein cattle.